The Effect of Financial Literacy and Financial Management Behavior on Financial Well-Being with Financial Satisfaction as an Intervening Variable (Study on MSMEs Madura Coastal Area) - M. Boy Singgih Gitayuda (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
The objective of this study was to investigate the impact of financial literacy and financial satisfaction on financial well-being, considering financial management behavior as an intervening variable. The data were analysed using quantitative methods, employing descriptive and associative approaches. Information was gathered through interviews and questionnaire responses from 60 micro, small, and medium-sized enterprise (MSME) actors in the Madura coastal area, specifically in Pamekasan and Sumenep districts. The data were processed using SmartPLS 3.0 software. The study's results reveal several key findings: financial literacy has a significant influence on financial satisfaction; however, there is no observed impact of financial management behavior on financial satisfaction. Additionally, financial literacy influences financial well-being, but financial management behavior does not exhibit a significant effect on financial well-being. Furthermore, no direct effect of financial satisfaction on financial well-being was identified. There is also no indirect effect of financial literacy on financial well-being through financial satisfaction, and similarly, there is no indirect effect of financial management behavior on financial well-being through financial satisfaction.